Uncontrolled diabetes mellitus: a current understanding of the mechanisms underlying the disease that affect orthodontic tooth movement - SAMARTINI,Daniela Gomides (2021)
ABSTRACT With improvements in dental aesthetic requirements an increasing number of adults are seeking orthodontic treatment that, along with current lifestyle and eating habits of the adult population, makes orthodontists more likely to encounter patients with metabolic disorders such as diabetes mellitus. Speculated that the diabetic patient during orthodontic treatment may not experience a physiological healing process as a healthy patient. Therefore, the objective of this work is to present a current and contextualized review of the mechanisms by which uncontrolled diabetes mellitus impacts on bone remodeling and orthodontic tooth movement during the application of orthodontic forces. The following databases were searched MEDLINE (via PubMed), Scopus, Web of Science, SciELO, LILACS and open grey with these MeSH “bone remodeling”, “diabetes mellitus”, “orthodontic” and “tooth movement”. Five articles remained after search strategy and were analyzed. In sum, no clinical studies were found, the evidence was limited to animal studies (rats). The results suggest that there are differences in bone remodeling and tooth movement during the application of orthodontic forces in animals with diabetes mellitus when compared to healthy animals, especially when the disease is associated with periodontal disease. However, the results are still controversial and may be due to different study protocols.